Analysis of the asymmetric behavior of propeller–rudder system of twin screw ships by CFD. (1st October 2017) - Muscari, Roberto; Dubbioso, Giulio; Viviani, Michele; Di Mascio, Andrea
Abstract: The interference between the hull, propeller and rudder remarkably affects the control and maneuvering capabilities of marine vehicles. In case of twin screw/twin rudder ships, the asymmetric evolution of the wake past the hull causes the asymmetric functioning of the propeller–rudder system. Systematic investigations on this aspect for twin screw ships are limited. Available experimental data carried out on simplified hull–propeller–rudder system and captive model tests do not allow to completely understand the fluid mechanism at the basis of the hydrodynamic interaction that should be taken into account in simplified maneuvering mathematical models for preliminary predictions. In this paper the hull–propeller–rudder interactions phenomena for a twin screw/twin rudder model are investigated by URANS simulations, with a particular focus on the asymmetry of the propeller–rudder system. To this aim, captive model tests consisting of pure rudder and coupled drift–yaw motions corresponding to the steady phases of turning circle maneuvers at different rudder angles ( δ = 15 ° ÷ 35 ° ) are performed at the speed correspondent to Fr =0.265. Moreover, a free running maneuvering simulation is also performed to gain more insight on the transient phase of the maneuver. An identity rudder lift methodology is applied to synthesize the hull–propeller–rudder interactions by means of a flow straightening coefficient; the analysis highlights that these effects are weak and invariant with respect to the rudder angle on the windward shaft, whereas on the leeward side these effects are extremely sensitive to the evolution of the hull and propeller wake. Abstract : Graphical abstract: Abstract : Highlights: Focus on the performance of the propeller-rudder system of a twin screw model. Asymmetric generation of control forces depends on ship motion and propeller loading. Comparison of hull-propeller-rudder interferences during steady and unsteady motions.